A longitudinal and cross‐sectional study of plasma neurofilament light chain concentration in Charcot‐Marie‐Tooth disease. Issue 1 (9th December 2021) - Rossor, Alexander Martin; Kapoor, Mahima; Wellington, Henny; Spaulding, Emily; Sleigh, James N.; Burgess, Robert W.; Laura, Matilde; Zetterberg, Henrik; Bacha, Alexa; Wu, Xingyao; Heslegrave, Amanda; Shy, Michael E.; et al.
Abstract: Advances in genetic technology and small molecule drug development have paved the way for clinical trials in Charcot‐Marie‐Tooth disease (CMT); however, the current FDA‐approved clinical trial outcome measures are insensitive to detect a meaningful clinical response. There is, therefore, a need to identify sensitive outcome measures or clinically relevant biomarkers. The aim of this study was to further evaluate plasma neurofilament light chain (NFL) as a disease biomarker in CMT. Plasma NFL was measured using SIMOA technology in both a cross‐sectional study of a US cohort of CMT patients and longitudinally over 6 years in a UK CMT cohort. In addition, plasma NFL was measured longitudinally in two mouse models of CMT2D. Plasma concentrations of NFL were increased in a US cohort of patients with CMT1B, CMT1X and CMT2A but not CMT2E compared with controls. In a separate UK cohort, over a 6‐year interval, there was no significant change in plasma NFL concentration in CMT1A or HSN1, but a small but significant reduction in patients with CMT1X. Plasma NFL was increased in wild type compared to GARS C201R mice. There was no significant difference in plasma NFL in GARS P278KY compared to wild type mice. In patients with CMT1A, the small difference in cross‐sectional NFL concentration vs healthy controls and the lack of change over time suggests that plasma NFL may lack sufficient sensitivity to detect a clinically meaningful treatment response in adulthood.